YEAR-TO-YEAR DYNAMICS OF THE ICE COVER ANOMALIES IN THE TATAR STRAIT FOR THE PERIOD FROM 1882 TO 2018 - V. M. Pishchalnik; D. V. Dorofeeva; I. G. Minervin; I. V. Shumilov; I. V. Nikulina (Известия ТИНРО, 2019)
Interannual variations of the ice cover in the Tatar Strait are analyzed for the period from 1882 to 2018 and compared with the ice cover dynamics in the Okhotsk Sea. Synchronicity of the ice cover long-term oscillations in these regions is noted for the periods of 1894–1920 and 1985–2009, but it is not statistically significant for the whole time series. Current trend to the ice cover decreasing began in the Tatar Strait 5 years later than in the Okhotsk Sea. Besides, the cases of extremely low ice cover were observed in the Tatar Strait along the whole period of observations, whereas were happened in the Okhotsk Sea only in the period of warming since 1990s. Possible influence of the Amur River runoff on the sea ice forming in the Tatar Strait is discussed.